2005
DOI: 10.1016/j.jom.2005.09.006
|View full text |Cite
|
Sign up to set email alerts
|

TQM practice in maquiladora: Antecedents of employee satisfaction and loyalty

Abstract: In this study, we investigate the transferability of TQM practices to offshore manufacturing firms by validating direct and indirect relationships among top management commitment, HR-focused TQM practices, employee satisfaction, and employee loyalty. Our research objective is to isolate critical TQM practices that would enhance employee satisfaction and loyalty among maquiladora workers. On-site surveys were conducted at two leading maquiladora firms that have long implemented TQM. The statistical results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
205
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(246 citation statements)
references
References 93 publications
28
205
2
11
Order By: Relevance
“…They also proved that TQM in supply chain is significant to ameliorate key elements such as quality, delivery and lead-time. Besides that, Jun et al (2006) showed that the firms with human resources that concentrate in TQM methods can raise employee satisfaction. The striking improvements in employee satisfaction resulted to a higher level of customer's devotion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also proved that TQM in supply chain is significant to ameliorate key elements such as quality, delivery and lead-time. Besides that, Jun et al (2006) showed that the firms with human resources that concentrate in TQM methods can raise employee satisfaction. The striking improvements in employee satisfaction resulted to a higher level of customer's devotion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Maurer (2001) rewards and recognition are essential factors in enhancing employee job satisfaction and work motivation which is directly associated to organizational achievement (Jun et al, 2006). Kalimullah Khan conducted a study in which he examined the relationship between rewards and employee motivation in commercial banks of Pakistan.…”
Section: Recognition and Employee Motivationmentioning
confidence: 99%
“…The management commitment items were from Daily, et al (2003Daily, et al ( , 2007, Grandzol and Gershon (1998) and Wee and Quazi (2005). The empowerment items were from Ahire and O'Shaughnessy (1998), Daily, et al (2003Daily, et al ( , 2007, Grandzol and Gershon (1998), Howard and Foster (1999), Jun, Cai and Shin (2006), Wee and Quazi (2005). The feedback and review items were from Chinander (1997), Flynn, Schroeder and Sakakibara (1994), Howard and Foster (1999), Ramus (2001), Ramus and Steger (2000), Wee and Quazi (2005).…”
Section: Survey Instrumentmentioning
confidence: 99%
“…The coordinators were responsible for selecting employees, distributing and collecting questionnaires from the company. The stratified sampling approach was utilized in order to achieve heterogeneity among respondents to reduce the common survey bias (Jun, Cai & Shin, 2006). The sub grouping criteria are organizational level and work-departments.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation